(untitled) (Pulse, 2014)
Coronary Artery Bypass Surgery (CABG) is an established surgical treatment of coronary artery disease. Conventionally it has been done with left internal mammary artery and saphenous vein for many years. But the study shows that the rate of stenosis of venous graft is much higher than arterial graft in 10 years after CABG1 Recent studies also proved that the outcome of total arterial grafts for CABG is much better than conventional CABG2 In my recent short practice in this hospital, it also proved to be a safe procedure with better early post operative results. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20186 Pulse Vol.5 January 2011 p.27-29